A REVIEW OF THE IMPLEMENTATION OF THE PUSKESMAS MANAGEMENT INFORMATION SYSTEM (SIMPUS) AT PAMULANG HEALTH CENTRE - Firmansyah, Miftah Parid; Rahmayeni, Windi; Adha, Muhammad Zulfikar; Utama, Timor (STIKes Widya Dharma Husada Tangerang, 2025)
SIMPUS is an arrangement that provides information to assist the decision-making process in carrying out health center management in achieving its target activities. The implementation of RME requires an element of SM management related to its implementation aimed at identifying the application of RME both promotive, preventive, curative and rehabilitative. The purpose of the study was to determine the implementation of SIMPUS at Pamulan Health Center. The type of research used is descriptive method with a qualitative approach ... The sample used 5 officers consisting of SIMPUS admin staff, Medical Records officers, Nurses, Doctors and Pharmacy. This research instrument uses observation and interviews. The results of the study were obtained by interviews using SM elements at Pamulang Public Health Center in the Implementation of the Puskesmas Management Information System has been running well, but there are still some that are not in accordance with Permenkes 24 of 2022 article 13 paragraph (1) and have not met the RME standards with there are still obstacles from several aspects, namely in the aspect of mnø there is only one officer with a medical record education background and is no special training for all officers, There are still constraints, machines still have menus that cannot be used, methods aspects already have SOPs related to the flow of SIMPUS operations,the aspect of unstable internet connectivity and money aspects related to the budget have been budgeted annually through the South Tangerang City Health Office government. Suggestions related to the constrained SM elements, namely the man element, all officers attend training to improve their ability to operate SIMPUS, materials provide their own internet and carry out regular checks and repairs for the network system and machines request access rights permission for menus that cannot be used.A REVIEW OF THE IMPLEMENTATION OF THE PUSKESMAS MANAGEMENT INFORMATION SYSTEM (SIMPUS) AT PAMULANG HEALTH CENTRE